The Influence Of Accessibility, Online Promotion, And Product Reviews On Purchasing Decision With The Intervening Variable Of Purchase Intention On Shopee Application - Sari, Desti Rupita; Ariska , Yesi Indian; Abi, Yudi Irawan (Journal of Management, Economic, and Accounting, 2024)
This study aims to examine the factors that influence purchasing decisions in the Shopee application. The focus of this study is to determine whether accessibility, online promotions and product reviews on purchasing decisions with the intervening variable of purchase intention on shopee application. The results of this study that accessibility variable has no effect on purchasing decisions on shopee application, the online promotion variable affects purchasing decisions on shopee application, the product review variable affects purchasing decisions on shopee application, accessibility affects buying interest as an intervening variable, online promotion has no effect on purchase intention as an intervening variable, product review affects purchase intention as an intervening variable, accessibility affects purchasing decisions through purchase intention as an intervening variable, online promotion has no effect on purchasing decisions through purchase intention as an intervening variable, product reviews have no effect on purchasing decisions through purchase intention as an intervening variable, and purchase intention variables have no effect on purchasing decision variables.